The Impact of Total Factor Productivity on Economic Growth for Developed and Emerging Countries: A Second-generation Panel Data Analysis. (November 2017) - Yalçınkaya, Ömer; Hüseyni, İbrahim and Çelik, Ali Kemal
This article investigates the determinants of economic growth and also seeks to determine whether or not the impact of total factor productivity (TFP) changes with respect to the level of development for selected countries. In this manner, the present study examines the impact of gross fixed capital formation, employed labour and the TFP of G-7, G-12 and G-20 countries on real GDP per capita using second-generation panel data analyses over the period 1992–2014. The results reveal that TFP has a greater impact on economic growth than fixed capital formation and employed labour for all country groups. Furthermore, the impact of TFP on economic growth was found to be greater for developed countries than for emerging countries. JEL Classification: C21, C22, C23